(3COH GdbVGAs - (3GHf CHj GdOe , EHQGgje Hf YHO Gddg Hf YHO GdefYe GdgePGfj GdMehj, GHf CHj GdOe,J (B642 (3g` s ((3eMeO Hf eMeO Hf HgGOQ s)
(3ChdgG (B:s
(3hHYO aEf Chdi eG CYedJ ajg GdbQGFM hYdbJ Hg GdCacGQ GddhGbM hYde aQhY GdTQjYI ef GdMdGd hGdMQGe s
(3BNQgG (B:s
(3hGddg YR hLd gh GdeSFhd Cf jYUefG ef GdRdd hjhabfG dUGdM Gdbhd hGdYed Hefg hcQeg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B49 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B53s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfajs